Family support in stroke rehabilitation (中风康复期家庭支持的应用研究) - LI Silu (李思璐); YANG Yanni (杨燕妮); LI Yanjun (李艳君) (Association of Integrative Nursing, 2022)
This paper introduced the application of family support in stroke rehabilitation. The concept of family support, evaluation tools and role of family support in improving recovery of stroke patients were summarized, in order to provide reference for further researches of interventions on stroke rehabilitation. (本文对家庭支持在中风患者康复期的应用进行总结, 包括家庭支持的概念、评估工具以及家庭支持在中风患者康复期发挥的作用, 以进一步探究家庭支持对中风康复期患者的有效方法及意义。)